A SARS‐CoV‐2 EG.5 mRNA vaccine induces a broad‐spectrum immune response in mice - Hongyu Wang; Qinhua Peng; Xinxian Dai; Zhifang Ying; Xiaohong Wu; Xinyu Liu; Hongshan Xu; Jia Li; Leitai Shi; Jingjing Liu; Yunpeng Wang; Danhua Zhao; et al. (MedComm)
Abstract The emerging of emergent SARS‐CoV‐2 subvariants has reduced the protective efficacy of COVID‐19 vaccines. Therefore, novel COVID‐19 vaccines targeting these emergent variants are needed. We designed and prepared CoV072, an mRNA‐based vaccine against SARS‐CoV‐2 Omicron (EG.5) and other emergent SARS‐CoV‐2 subvariants that encodes the EG.5 spike protein. Six‐week‐old female BALB/C mice were used to assess humoral and cellular immune responses and cross‐reactive neutralizing activity against various SARS‐CoV‐2 subvariants. Meanwhile different immunization strategies and doses were performed to detect the immunogenicity of this mRNA vaccine. Our results show that two doses of 5 µg CoV072 or a single dose of 15 µg CoV072 both induced broad‐spectrum cross‐protection ability in mice. Compared with a single dose of 15 µg CoV072, two doses of 5 µg COV072 exhibited higher levels of pseudovirus neutralizing antibody (PNAb) and cross‐reactive IgG responses to multiple variants. Moreover, higher levels of neutralizing antibody (NAb) against live XBB and EG.5 variants were also induced. Th1‐biased cellular immune response was induced in all vaccination groups. The antigen design and immunization strategy of this study have reference significance for the research of the next generation of COVID‐19 vaccine and other vaccines.